2014
DOI: 10.1126/science.1245711
|View full text |Cite
|
Sign up to set email alerts
|

Precise and Ultrafast Molecular Sieving Through Graphene Oxide Membranes

Abstract: Graphene-based materials can have well-defined nanometer pores and can exhibit low frictional water flow inside them, making their properties of interest for filtration and separation. We investigate permeation through micrometer-thick laminates prepared by means of vacuum filtration of graphene oxide suspensions. The laminates are vacuum-tight in the dry state but, if immersed in water, act as molecular sieves, blocking all solutes with hydrated radii larger than 4.5 angstroms. Smaller ions permeate through t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

50
1,831
2
13

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,211 publications
(1,896 citation statements)
references
References 52 publications
50
1,831
2
13
Order By: Relevance
“…However, at the gap between the edges of non-interlocked neighboring GO sheets and, at the cracks and holes of the sheet, they can diffuse perpendicular to the GO sheets and permeate through the membrane. 18,55 Thus, such structural defects supplement the role of the interlayer nanochannels in the separation of the ions and molecules. Moreover, oxygen-containing functional groups on the GO sheets are ionized in the wet state and thus negatively charged.…”
Section: Multilayer Graphene Desalination Membranesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, at the gap between the edges of non-interlocked neighboring GO sheets and, at the cracks and holes of the sheet, they can diffuse perpendicular to the GO sheets and permeate through the membrane. 18,55 Thus, such structural defects supplement the role of the interlayer nanochannels in the separation of the ions and molecules. Moreover, oxygen-containing functional groups on the GO sheets are ionized in the wet state and thus negatively charged.…”
Section: Multilayer Graphene Desalination Membranesmentioning
confidence: 99%
“…55 In this regard, the interlayer spacing of the GO sheets has a key role. Although in graphite, which is composed of pristine graphene sheets, the interlayer spacing in dry state is only 3.4 Å, the presence of oxygen-containing functional groups on the GO sheets increases this spacing to 6-7 Å.…”
Section: Multilayer Graphene Desalination Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it was found that sub-micrometer-thick graphene oxide (GO) membranes were almost impermeable to liquids, vapors, or gases but allowed unimpeded permeation of water [1] because of the nearly frictionless flow of water molecules through the two-dimensional hydrophobic nonoxidized capillaries. Moreover, it was further demonstrated that GO membranes could act as molecular sieves to block all solutes with hydrated radii > 0.45 nm when immersed in water [2], in which size exclusion appears to account for this behavior. For smaller sizefitted solutes that can enter in nanochannels, GO membrane could achieve more accurate ion selectivity via the diverse interactions between ions and sp 2 clusters or oxygen-containing functional groups on GO basal planes [3].…”
Section: Graphene-based Membranes For Organic Solvent Nanofiltrationmentioning
confidence: 99%
“…A schematic representation of the desalination of salt water is shown in Figure 6. R. K. Joshi et al studied the permeation of water through micrometer thick GO laminates prepared using a vacuum filtration technique (112). The GO laminates act like a molecular sieve which block all solute particles possessing a hydrated diameter greater than 4.5 Å.…”
Section: Graphene Carbon Nanotubes and Their Composites Used In Watmentioning
confidence: 99%